2022
DOI: 10.1111/efp.12725
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring foliar symptom expression in beech leaf disease through time

Abstract: Beech leaf disease (BLD) is a recently discovered disease that is causing severe damage to American beech trees (Fagus grandifolia Ehrh.) in northeastern North America (Ewing et al., 2019). Due to the novelty of the disease, information on the general epidemiology and symptom phenology of BLD is largely unavailable.Beech leaf disease is characterized by two distinct symptom types: (1) a normal size leaf with dark green, interveinal bands that may manifest between a few or many veins and cover up to two thirds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…Based on our observations in the field and previous work (Fearer et al., 2022; Volk et al., 2019), the most severely symptomatic leaves senesce early, meaning that these are shed in favour of growing new leaves. The trigger of this is not known, but with high levels of abscisic acid (ABA) associated with leaf death in diverse land plants (McAdam et al., 2022), the role of hormones such as ABA in triggering early leaf death as a result of BLD should be investigated.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Based on our observations in the field and previous work (Fearer et al., 2022; Volk et al., 2019), the most severely symptomatic leaves senesce early, meaning that these are shed in favour of growing new leaves. The trigger of this is not known, but with high levels of abscisic acid (ABA) associated with leaf death in diverse land plants (McAdam et al., 2022), the role of hormones such as ABA in triggering early leaf death as a result of BLD should be investigated.…”
Section: Discussionsupporting
confidence: 74%
“…Decreased photosynthetic rates in symptomatic leaves in combination with the increased mass allocation to symptomatic leaf tissue would lead to reduced net carbon gain in the short term, and may cause depletion of the trees' stored carbon and an inability to sustain growth in the long term. Another symptom of BLD is increased bud abortion leading to canopy thinning (Fearer et al., 2022), which in combination with the low photosynthetic rates of the remaining leaves would substantially limit the trees' net carbon gain. This combination may ultimately provide a mechanistic explanation for the observed decline in tree vigour post‐infection.…”
Section: Discussionmentioning
confidence: 99%
“…The more severe symptom expression is referred to as crinkling, where a leaf appears shrunken and deformed, with a thickened leathery feel and often bearing chlorotic tissue. Unlike many fungalborne foliar diseases, the symptoms of BLD do not progress throughout the duration of a growing season, such that the symptom presentation of individual leaves at the time of bud break is consistent through leaf senescence (Fearer et al, 2022b). Under a high severity of infection, thought to occur when nematode populations within the bud are exceptionally high, buds are aborted from the stem and leaves fail to flush out in the spring.…”
Section: Introductionmentioning
confidence: 99%
“…While the exact BLD disease cycle has not been clearly defined, studies show that LCM overwinters in American beech buds as well as attached and detached leaves; live nematodes are found in leaves throughout the growing season with the greatest numbers found in late summer/early fall (Carta et al, 2020;Reed et al, 2020). Since BLD symptoms are present at bud break and do not progress throughout the season (Fearer et al, 2022), this suggests that LCM causes symptoms prior to bud break, which Carta et al (2020) confirmed in their study, and LCM migration into the leaf occurs sometime before September (Reed et al, 2020). Therefore, it is possible that higher lignin levels in local-naïve leaves are preventing LCM/pathogen infection prior to bud break.…”
Section: Discussionmentioning
confidence: 99%
“…Beech leaf disease (BLD) was first detected on American beech (Fagus grandifolia) in Ohio in 2012 and has since spread throughout the northeastern United States and into Canada (Ewing et al, 2019). There are two characteristic symptoms of BLD, including an interveinal darkening of the leaf (i.e., banded symptoms) and a complete darkening and thickening of the entire leaf (i.e., crinkled symptoms) (Fearer et al, 2022). The presence of a new subspecies of nematode, Litylenchus crenatae ssp.…”
Section: Introductionmentioning
confidence: 99%